Corrosion inhibition of mild steel in 15 wt.% HCl by durum wheat - Ajayi, Olorunfemi; Everitt, Nicola; Voisey, K.T. (2017)
The toxicity of most commercial corrosion inhibitors and strict environmental legislations have required the development of environmentally-friendly, cheap and non-toxic inhibitors. The use of natural products, especially of plant origin as corrosion inhibitors has become an area of increasing research because plant extracts contain an incredibly rich source of natural chemical compounds which can be extracted by simple procedures at low-cost. Durum wheat was investigated in this work because functional groups were identified which suggested that it could be a promising potential inhibitor. The corrosion of mild steel in 15 wt.% HCl solution with and without Durum wheat was investigated and directly compared to results from two commercial corrosion inhibitors, propargyl alcohol and 2- mercaptobenzimidazole, under the same conditions, by comparing weight loss with and without inhibition. The durum wheat powder and adsorbed films were characterised by Fourier transform infrared spectroscopy (FTIR), and the exposed samples were characterised using SEM, EDS spectroscopy and surface profilometry. The effects of concentration, temperature (20-60°C) and immersion time (5-24 h) on the corrosion inhibition were investigated. Durum wheat was shown to be a successful green corrosion inhibitor with a room temperature inhibition efficiency of 97% (as compared to values of 99% and 97% for propargyl alcohol and 2 - mercapto benzimidazole respectively) and at a lower cost per l L of corrosive solution. However, at the severe corrosive conditions chosen for this research, the inhibition performance of both durum wheat and 2- mercaptobenzimidazole was influenced by time and temperature, and the durum wheat corrosion inhibition was reduced to 78% after 24 hours at 60°C, compared to 88% for 2- mercaptobenzimidazole. All the inhibitors investigated obeyed Langmuir adsorption isotherm.